Seed longevity and fire: post-germination responses of Rumex acetosella L. in northwest Patagonian grasslands (Argentina) - Franzese, Jorgelina (2014)
The cosmopolitan herb Rumex acetosella forms persistent soil seed banks and increases in cover after fire. We investigated how the interaction between seed age and fire affects seedling growth by exposing different-aged seeds to heat, smoke, charcoal, and ash treatments. We measured growth of germinated seedlings that were transplanted and allowed to grow for 65 days in a greenhouse. Seedlings from seeds >8 years old did not reach an appropriate radicle length for transplantation. Seedling growth decreased with increasing temperature of the heat treatment. As seed age increased, growth decreased with smoke and charcoal, and increased with ash treatment. Height was negatively correlated with seed age. Our results suggest that fire and seed age could affect demographic responses of R. acetosella seedling populations. Post-fire recruitment could be partially favored by the positive effect of nutrient input from ash on seedling growth. High fire intensities, however, would be detrimental to seedling vigor.